Tax benefits of the agricultural sector and peruvian social- economic development - Tuesta Bardalez, egundo Eloy (2021)
Objective: Determine the relationship between the agrarian sector’s tax benefits and the Peruvian economic and social development. Method: The study was based on the analytical and synthetic method of the quantitative variables’ relationships investigated under a non-experimental design, using documentary analysis and the statistical model of canonical correlation as techniques, considering public information, in a cross-sectional period (2005-2019). Results: The Hotellings indicator evidences a significant relationship of both groups of variables; however, before a disaggregated analysis, the correlations show questionable results compared to the results of the state of the art of the investigated topic. Conclusions: There are direct and significant relationships between the gross domestic product, the sector's exports, tax formalization and corporate income tax payments. There is no significant direct relationship between EsSalud Expenditures and the sector’s Labor Formalization, as well as between the Internal Tax Expenditures and Labor Formalization, which is supported by the statistical test of the canonical correlation between the variables proposed in this research.